The Role of Intellectual Capital in Achieving a Competitive Advantage: A Field Study on Jordanian Private Universities in the Northern Region (Global Journal of Management and Business Research, 2017)
This study aims to determine the role of intellectual capital and its elements (human capital, relational capital, structural capital) and to achieve the competitive advantage and its dimensions (quality, efficiency, innovation, responsiveness) in the Jordanian private universities in the northern region (Jadara university, Irbid national university, Jarash university, Philadelphia university),where the study sample (90) person of the total study population(120), so questionnaire was designed to verify approaches in the theoretical frameworks of the intellectual capital independent variable, and its relation to the dependent variables, which is the competitive advantage. The hypotheses were tested based on statistical analysis programs, one of the most important results of the study is the existence of a relation of statistical significant between intellectual capital and its three dimensions and achieving competitive advantage, where the study showed that the dimensions of human and social capital are more available than structural capital, so both of them are contributing in the competitive advantage more than structural capital.
Keywords: intellectual capital; competitive advantage; private universities; northern region; jordan